Investigation of Flux-Weighted Average Cross Sections for Reactions on Nb with Bremsstrahlung of LUE-75 - Avetisyan, A. E.; Avetisyan, R. V.; Barseghyan, A. G.; Gharibyan, Yu. A.; Gyurjinyan, A. V.; Dallakyan, R. K.; Kerobyan, I. A.; Mkrtchyan, H. A. (Physics of atomic nuclei, 2021)
Studies of the cross section of gamma-neutron reactions on the Nb nucleus were carried out on the bremsstrahlung of the linear electron accelerator LUE-75 which is located at the A. Alikhanyan National Science Laboratory (Yerevan Physics Institute). The experiment was done at 30 and 40 MeV bremsstrahlung end-point energies. The reaction cross sections for Nb Nb reactions were measured by the activation method with the spectrometric analysis using the High Purity Germanium detector (HPGe). The values of cross sections for different energies of photon beam were determined using the TALYS 1.95 and EMPIRE 3.2 nuclear codes. The energy distribution of photon spectra was performed using the GEANT4 package. The obtained experimental and theoretical results are compared with the available experimental data of other authors. Good agreement was observed between the theoretical and experimental data. The data on the reaction cross section for Nb Nb were obtained for the first time.